Design of low quantum cost reversible BCD adder - Cheng, C.; Gopal, Lenin; Sidhu, Amandeep; Singh, A. (2016)
Reversible logic is one of the emerging computational methodologies which assures zero power dissipation through theoretical laws of thermodynamics. It has received significant interest in application on quantum computing, nanotechnologies and low power computing devices. In this work, we present a reversible logic implementation for Binary Coded Decimal (BCD) adder which is designed to obtain lowest quantum cost value. Other parameters such as ancilla input, garbage output and delay are kept at minimal. Experiment result shows that the proposed work outperforms other designs in terms of quantum cost. Considering for a 1 digit BCD adder, it has a 4% improvement in terms of quantum cost compared to the current best existing ones. The improvement range increases as the BCD digit becomes larger.